2012
DOI: 10.1017/s0142716412000574
|View full text |Cite
|
Sign up to set email alerts
|

The role of age of onset and input in early child bilingualism in Greek and Dutch

Abstract: The focus of this study is the acquisition of grammatical gender in Greek and Dutch by bilingual children whose other language is English. Although grammatical gender languages share the property of noun classification in terms of grammatical gender, there are important differences between the languages under investigation here in terms of both the morphological cues for gender marking available to the child and the developmental path followed by monolingual children. Dutch offers limited input cues for gramma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
177
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(203 citation statements)
references
References 70 publications
17
177
3
6
Order By: Relevance
“…This delay can be attributed to the opacity of gender assignment in Norwegian. This corresponds to what has been found for Dutch (another language with arbitrary gender assignment), where neuter gender has been shown to be problematic until approximately the age of six (Blom et al 2008;Unsworth et al 2014;Tsimpli & Hulk 2013). Interestingly, neuter gender marking on indefinite articles is shown to be acquired early in German, by age three (Müller 1990(Müller , 1999, despite the fact that grammatical gender is relatively opaque (Hopp 2012).…”
Section: Discussionsupporting
confidence: 78%
“…This delay can be attributed to the opacity of gender assignment in Norwegian. This corresponds to what has been found for Dutch (another language with arbitrary gender assignment), where neuter gender has been shown to be problematic until approximately the age of six (Blom et al 2008;Unsworth et al 2014;Tsimpli & Hulk 2013). Interestingly, neuter gender marking on indefinite articles is shown to be acquired early in German, by age three (Müller 1990(Müller , 1999, despite the fact that grammatical gender is relatively opaque (Hopp 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, while monolingual children eventually acquire the target system, it is unclear whether bilingual children ever proceed beyond this stage of overgeneralization. Since gender has to be acquired in an item-based fashion in Dutch, the relevant factor for successful acquisition is likely to be amount of exposure rather than age of onset (see Unsworth, 2013, andUnsworth, Argyri, Cornips, Hulk, Sorace, &Tsimpli, 2011). This may be similar for those nouns in French that are not covered by gender assignment rules.…”
Section: Monolingual and Bilingual Acquisition In Childrenmentioning
confidence: 99%
“…For example, L1 Dutch-speaking children have been shown to acquire gender much later than L1 Greek-speaking children due to the opacity of the Dutch gender system as opposed to the transparency and systematicity of the Greek gender system (Tsimpli & Hulk, 2013). The same asynchronous acquisition of the Dutch and the Greek gender systems has also been found in the context of childhood bilingualism by Unsworth et al (2014), who compared Greek and Dutch 2L1 and L2 children with English as their L1. Conversely, the study by Chondrogianni et al (2015) reported that Turkish-speaking children in the Netherlands and the UK acquiring L2 Dutch and L2 English definite articles respectively followed the same developmental patterns, due to the similarities of the semantic properties of the definite article systems in Dutch and in English.…”
Section: Cross-linguistic Aspects In Child Second Language Acquisitionmentioning
confidence: 88%